Keterlibatan Siswa Terhadap Pelaksanaan P5 dan Pembelajaran Kewirausahaan dalam Meningkatkan Minat Berwirausaha di SMA Negeri 11 Semarang - Khasanah, Nuriyah; Pitaloka, Lola Kurnia (Business and Accounting Education Journal, 2025)
The purpose of this research is to describe and analyze student engagement in the implementation of P5 and entrepreneurship education in increasing entrepreneurial interest at SMA Negeri 11 Semarang. This research uses a descriptive qualitative approach with a case study design. The data and sources used come from entrepreneurship subject teachers and 5 students each from grade 10 and 11. Data collection techniques include semi-structured interviews. The data validity techniques used are credibility, transferability, dependability, and confirmability. Data analysis techniques include data reduction, data condensation, data presentation, and conclusion drawing. The results of the study show that student engagement in P5 and entrepreneurship education produces students who are responsible, active, confident, and courageous in making decisions and asking questions. Students are able to understand the meaning of entrepreneurship, leading to their interest in engaging in entrepreneurial activities. The recommendation for this research is that the school needs to improve the facilities and infrastructure to support practical activities and conduct regular evaluations to identify and improve any deficiencies.